Analysis of Scientific Papers Included in the Sciences Citation Index Expanded Written by South Korean Plastic Surgeons: 2001-2010 - Ju Young Go; Goo-Hyun Mun; Byung-Joon Jeon; So-Young Lim; Jai-Kyong Pyon; Sa-Ik Bang; Kap Sung Oh; Myoung-Soo Shin (Archives of Plastic Surgery, 2012)
Background The purpose of our study was to analyze scientific papers published by South Korean plastic surgeons in journals included in the Science Citation Index Expanded (SCIE), and to evaluate the publication and research activities of Korean plastic surgeon. Methods We conducted a survey of SCIE papers in the field of plastic surgery published by South Korean authors between 2001 and 2010 using Web of Science software. We further analyzed these results according to the number of publications per year, journals, institution, and type of papers. We also compared the total number of citations to published scientific papers. We analyzed the rank of South Korea among other countries in representative journals. Results Overall, 667 papers were published by South Korean authors between 2001 and 2010. The number of publications increased dramatically from 2003 (n=31) to 2010 (n=139). Subsequently, the ten most productive Korean medical colleges were identified. All published papers received 2,311 citations and the citation to paper ratio was 3.49. The rank of Korea among other countries in terms of the number of published papers remained in the top 10 during the recent 10 years. Conclusions Publication output of Korean plastic surgeon over the last 10 years showed a remarkable growth in terms of quantity and quality. Currently, Korea is among the top six countries in representative plastic surgery journals. Korean plastic surgeons have played a central role in this progress, and it is anticipated that they will continue to do so in the future.